Analysis of risk factors associated with fatal intersection crashes involving older drivers in the Midwest - Alshehri, Abdulaziz Hebni (Kansas State University, 2022)
Motor vehicles are the primary source of transportation in the United States. While this is true for any age group, the older population tend to rely more heavily on automobiles because of easy access and availability, compared to public transportation even when it is available. Older drivers aged 65 years and older are more vulnerable to fatal crashes due to cognitive impairments and frailty. When older drivers are involved in crashes, they sustain higher injury severities compared to younger drivers. One location where older driver experience higher crash risk is intersection, due to the complexity of the situation involving multiple tasks and movements. The objectives of this study were to determine risk factors associated with intersection-related crashes involving older drivers in the Midwestern states and to provide countermeasure ideas to improve safety. Five-year fatal crash data from 2014 to 2018 from the Fatality Analysis Reporting System (FARS) database were utilized, and statistical analysis was carried out to identify characteristics of fatal crashes involving older drivers and risk factors associated with intersection crashes among this age group. Three separate binary logistic regression models were developed to identify statistically significant predictor variables. First model represents older drivers who are involved in fatal single-vehicle crashes. Second model represents fatal multi-vehicle crashes involving at least one older driver, whereas the third model represents fatal single-vehicle crashes involving drivers younger than 65 years for comparison purposes. The dependent variable is whether a fatal crash occurs at an intersection location or not. Many independent variables that include various crash, driver, vehicle, and environmental factors were considered. By considering a 95 percent confidence level, odds ratios were estimated and used to identify relative risk factors of fatal intersection crashes. Analysis showed that controlled intersections, two-way undivided highways, and roads with posted speed limits less than 55 mph increased the risk of fatal single-vehicle and multi-vehicle crashes for older drivers. Fatal single-vehicle crashes were especially prevalent for these drivers. Factors such as urban roadways, driver age older than 75 years, nighttime driving, and speeding increased the risk of single-vehicle fatal intersection crashes, while turning movements and intersecting paths, straight and level roadways, two-lanes highway, and violation of roadway rules increased the risk of multi-vehicle fatal intersection crashes for older drivers. Single-vehicle fatal intersection crash analysis also showed that controlled intersections, two-way undivided highways, roads with posted speed limits less than 55 mph, urban roadways, speeding, nighttime driving, and fixed objects increased the risk of intersection-related fatal single-vehicle crashes, especially for older drivers. However, factors such as straight and level roadways, impaired driving, driver obesity, and the operation of recreation vehicles, buses, or motorcycles increased the risk of single-vehicle fatal intersection crashes for drivers in other age categories. Based on model results, countermeasure ideas to improve the safety of older drivers at intersections as well as other road users were identified. Among suggested ideas, improving intersections designs to accommodate older driver needs is recommended, such as implementing roundabouts when it is appropriate, reach minimum of 75-degree skew angel at intersection, providing protected left turn signals, flashing yellow arrow, restricted crossing U-turn, median U-turn, using rumble stripes along the side of roadway and median, providing transverse rumble strips (TRS) at intersections, improving roadway lighting, signs and markings at intersections and interchanges, implementing roadway diet, enhancing roadway signs and retroreflective delineation, providing cable, guardrail, or concrete barriers, implementing continuous raised-curb medians, enhancing lane drop marking on interchanges, providing acceleration and deceleration lane for merging and diverging locations, providing fixed or portable changeable message signs, enhancing high friction surface treatments on risk prone locations, increasing contrast markings on concrete pavement. Beside the engineering countermeasures, using newer vehicles that equipped with many safety features is advisable to enhance older and other drivers’ safety. In addition, older driver license renewal may be modified to be required yearly to overcome early signs of fatigue or cognitive decline to reduce fatal crash risks and enhance safety. Therefore, the results and suggested countermeasures can provide guidance to improve safety of older drivers and other road users.
Keywords: Older driver; Fatal injury; Midwest; Midwestern region; Traffic safety; Intersection fatal crash